Efektivitas Terapi Hipnotis 5 Jari dalam Penurunan Tingkat Kecemasan Akibat Hipertensi - Edo Gusdiansyah; Welly Welly (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Community Mental Health Nursing (CMHN) is one of the efforts used to help the community solve mental health problems (psychosocial) with promotive and preventive efforts that involve families. Many psychosocial problems occur in the community, namely anxiety, the global prevalence of anxiety is 11.6% of the total population of Indonesia or around 24,708,000 people. Efforts to reduce anxiety are by giving generalist therapy to control five-finger hypnosis anxiety. The purpose of its implementation is to provide inner peace for individuals, reduce anxiety, worry and anxiety, reduce tension, reduce blood pressure, lower heart rate, and sleep soundly. The implementation of 5 finger hypnosis was carried out in 4 meetings. This activity was carried out on 27 June 2022 with 20 elderly participants. The results of the evaluation showed that there was a decrease in the level of anxiety in the elderly at the pretest and posttest. A suggestion for the Public Health Center (Puskesmas) is to monitor the results of this education.